Cognitive aid use improves transition of care by graduating medical students during a simulated crisis. Issue 1 (1st January 2016) - Bauer, Brooke; Rebel, Annette; Dilorenzo, Amy; Schell, Randall M.; Dority, Jeremy S.; Lukens, Faith; Sloan, Paul A.
Abstract : Background: Residents are expected to have transition of care (ToC) skills upon entering graduate medical education. It is unclear whether experience and training during medical school is adequate. Objective: The aim of the project was to assess: 1) graduating medical students' ability to perform ToC in a crisis situation, and 2) whether using a cognitive aid improves the ToC quality. Methods: The authors developed simulation scenarios for rapid response teams and a cognitive aid to assist in the ToC during crisis situations. Graduating medical students were enrolled and randomly divided into teams of three students, randomly assigned into one of two groups: teams using a cognitive aid for ToC (CA), or not using a cognitive aid (nCA). In the scenario, teams respond to a deteriorating patient and then transfer care to the next provider after stabilization. Three faculty reviewed the recording to assess completeness of the ToC and the overall quality. A completeness score was expressed as a fraction of the maximum score. Statistical analysis was performed using a t -test and Mann-Whitney U test. Results: A total of 112 senior medical students participated: CA n =19, nCA n =17. The completeness score of the ToC and overall quality improved when using the cognitive aid (completeness score: CA 0.80±0.06 vs. nCA 0.52±0.07, p <0.01; ToC quality: CA 3.16±0.65 vs. nCA 1.92±0.56, p <0.01). Participants' rating of knowledge and comfort with the ToC process increased after the simulation. Conclusion: The completeness of information transfer during the ToC process by graduating medical students improved by using a cognitive aid in a simulated patient crisis.